Enhancing hydrogen adsorption performance of hollow silica spheres through the addition of Fe: A study on kinetic and thermodynamic - Saeid, Mohammed Faraj; Abdulkadir, B. A.; Herma Dina, Setiabudi (Elsevier Ltd, 2025)
Hydrogen is a clean and renewable energy carrier with the potential to address global energy and environmental challenges. However, its practical implementation is hindered by the lack of efficient storage solutions, as hydrogen has a low energy density by volume under ambient conditions. Enhancing hydrogen storage capacity is crucial for enabling its widespread use in applications. Current porous scaffold materials, such as metal-organic frameworks (MOFs) and zeolites, face significant limitations, including low adsorption capacity under practical operating conditions and slow kinetics. Hollow nano-silica (HSS) has emerged as a promising scaffold for hydrogen storage; however, its low capacity hinders practical implementation. To address this, iron (Fe) was incorporated into the HSS for its high capacity, availability and rapid sorption kinetics, which facilitate the dissociation of H2 molecules into atomic hydrogen and enhance chemical interactions between Fe and the HSS surface, thereby increasing the availability of active sites and improving hydrogen adsorption capacity. The resulting HSS exhibited a high surface area of 904 m2/g, with highly developed porous structures with a pore volume of 0.87 cm3/g, and an average pore diameter of 3.1 nm. Different amounts of Fe (3–10 wt%) were incorporated into the HSS. To examine the Fe loading effect, the physicochemical properties such as crystal phase, chemical structure, textural properties, and morphology of the Fe-modified scaffold were analysed. Hydrogen adsorption experiments were subsequently conducted under varying reaction conditions. Following the models of Van't Hoff and Langmuir, the kinetic, as well as thermodynamic analyses, were performed. The characterization findings revealed that the Fe was uniformly distributed within the HSS without causing any alterations to the original structure. Optimal hydrogen adsorption, reaching 2.42 wt%, was achieved with a 5.0 wt% Fe loading, 0.1 g catalyst loading, and at a 523 K temperature. Kinetic results showed that the adsorption followed a pseudo-second-order model, suggesting that the adsorption rate is likely governed by the availability of adsorption sites and the interactions between hydrogen and the adsorbent surface. The 5%Fe-HSS adsorbents demonstrated strong reusability, with less than a 6.4 % loss in activity after four consecutive cycles. These findings suggest that incorporating Fe into the silica structure is an efficient approach for improving the hydrogen adsorption capacity of HSS.